Managing the human factor in agriculture: Motivation and control - Lapčević Goran; Nikitović Zorana (Trendovi u Poslovanju)
Agricultural production is one of the oldest industries and it has a particularly significant social role to feed the world's population, which is experiencing a steady increase. Thanks to the general social and technological progress, agriculture has experienced a dramatic productivity growth over the last 100 years, thus successfully fulfilling its role. Agricultural production is influenced by a number of factors, the most important being human, biological, climatic, of agricultural land and others. Since the most important human factor is one of these factors, as it depends on improving productivity, increasing agricultural production and profits on agricultural land, it is of particular interest to study the understanding of the human factor behavior in the work process. Therefore, the paper focuses on the Planned Behavior Theory of the human factor and its motivation. In agricultural systems in which the human factor is under sufficient control, that is, with a sufficiently constructed organizational structure, managerial motivation theories are recommended for motivation. For agricultural systems where the human factor is not under sufficient control, that is, they have insufficiently developed organizational structure or in which it is completely lacking, self-determination theory, which is an upgrade of the Planned Behavior Theory, which provides an explanation of prediction of human behavior.